Periodontal disease in children and adolescent with diabetes mellitus - Yaacob, Munirah; Dewi Ardini, Yunita; Mohamed Ali, Suhaila; Tin, Myo Han; Taib, Mai Nurul Ashikin; Md. Zain, Fuziah; Hong, Yeow Hua (2017)
Background: Diabetes mellitus (DM) is the major risk factor for periodontal disease (PD). PD includes a spectrum of disorders ranging from gingivitis to periodontitis. If undetected and left untreated the disease can lead to early tooth loss. Assessing PD health is beneficial for keeping good oral health, which affects on glycemic control of the children and adolescent with DM. Objectives: To evaluate the periodontal health status of Malaysian diabetic children and adolescents compared to healthy controls. Methods: Periodontal health related parameters were clinically assessed in 32 children and adolescents (10-19 years of age) with diabetes and 32 non-diabetic control subjects. Age, gender, Body Mass Index (BMI), CDC percentiles and smoking status matching were done and purposive sampling was applied. HbA1C (%) results within 3-6 months before oral health assessment was used to define glycemic control status of the subjects. A cross analysis and Independent sample-t test were applied to infer periodontal health status difference between cases and controls. Results: Most of the cases were Type-1 DM (68.8%) and diagnosed less than five years (68.2%). The cases had manifested an increased gingival inflammation and calculus significantly compared to controls. Regarding PD health assessment; clinical attachment loss (CAL), gingival index (GI), Modified Turesky Quigley Hein plaque index (TQHI) and bleeding on probing (BOP) were not significantly different between cases and controls except for probing pocket depth (PPD); mean of (SE) (1.81±0.13) compared to controls (1.65 ±0.06). Higher mean of (SE) GI (0.9±0.82) were also noticed among cases than those of (0.8±0.11) controls. Conclusion: Periodontal screening & prevention programs at early age for DM children and adolescent should be considered for both oral health and glycemic controls. A further study with controlling; Insulin treatment, types of DM, DM duration, and oral hygiene practice and dietary habits should be conducted for more valid results.